2019
DOI: 10.4254/wjh.v11.i9.689
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma staging systems: Hong Kong liver cancer vs Barcelona clinic liver cancer in a Western population

Abstract: BACKGROUNDEarly allograft dysfunction (EAD) after liver transplantation (LT) is an important cause of morbidity and mortality. To ensure adequate graft function, a critical hepatocellular mass is required in addition to an appropriate blood supply. We hypothesized that intraoperative measurement of portal venous and hepatic arterial flow may serve as a predictor in the diagnosis of EAD.AIMTo study whether hepatic flow is an independent predictor of EAD following LT.METHODSThis is an observational cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Liver cancer is the seventh most common primary malignancy and the third-ranked cause of cancer-related mortality worldwide (1), of which hepatocellular carcinoma (HCC) accounts for more than 90% (2). The Barcelona Clinic Liver Cancer (BCLC) staging system, by right of its prominent advantages in its prognostic prediction, has been widely adopted for treatment allocation in clinical practice (3,4). Due to dormant and asymptomatic characteristics, a large portion of the HCC patients are diagnosed at an advanced stage beyond the optimal indications of curative treatments like hepatectomy, liver transplantation, and radiofrequency ablation (RFA) (5).…”
Section: Introductionmentioning
confidence: 99%
“…Liver cancer is the seventh most common primary malignancy and the third-ranked cause of cancer-related mortality worldwide (1), of which hepatocellular carcinoma (HCC) accounts for more than 90% (2). The Barcelona Clinic Liver Cancer (BCLC) staging system, by right of its prominent advantages in its prognostic prediction, has been widely adopted for treatment allocation in clinical practice (3,4). Due to dormant and asymptomatic characteristics, a large portion of the HCC patients are diagnosed at an advanced stage beyond the optimal indications of curative treatments like hepatectomy, liver transplantation, and radiofrequency ablation (RFA) (5).…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal and gastric varices were diagnosed by esophagogastroduodenoscopy. The Barcelona Clinic Liver Cancer (BCLC) staging classification was used for tumor staging 18 …”
Section: Methods and Patientsmentioning
confidence: 99%
“…The Barcelona Clinic Liver Cancer (BCLC) classification, the most used in Western countries, and the Hong Kong Liver Cancer (HKLC) staging system, which was created as a treatment guidance for Asian patients with HCC and is mainly used in Asian countries. Both classification systems use parameters such as presence of extrahepatic vascular invasion, tumor size, and number of nodules to stage HCC and provide management recommendations [8][9][10][11] .…”
Section: Staging Systems For Hepatocellular Carcinomamentioning
confidence: 99%
“…Despite both classifications being widely used, their differences complicate the decision-making process for the transplant team when presented with an advanced HCC. In a recent Brazilian study [9] , 519 patients diagnosed with HCC were staged according to the BCLC and HKLC system with the aim to analyze therapeutic approach for different stages. The authors found that between both systems, there was high general agreement regarding therapeutic management of HCC in the Western population.…”
Section: Staging Systems For Hepatocellular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation